Evaluation of the effect of intraoperative tropisetron on postoperative rebound pain after brachial plexus block: a randomized controlled trial - Junli Liu; Mingming Liu; Shengnan Shi; Fei Jiang; Ye Zhang; Jing Guo; Xingrui Gong (PAIN Reports, 2024)
Abstract. Introduction:. Postoperative rebound pain after peripheral nerve block increases patient suffering and delays recovery after surgery. Objectives:. We tested whether the 5HT-3 receptor antagonist and α7nAChR agonist tropisetron could prevent postoperative rebound pain. Methods:. A total of 115 patients were randomized to receive 5-mg/5-mL tropisetron or the same volume of normal saline. Pain intensity was measured with the numerical rating scale of pain (NRS). Rebound pain was defined as a change from mild pain (NRS ≤ 3) measured in the postanesthesia care unit to severe pain (NRS ≥ 7) within 24 hours after peripheral nerve blockade. Logistic regression was used to identify relevant factors associated with postoperative rebound pain. Results:. Tropisetron did not affect the NRS score or the incidence of rebound pain after peripheral nerve block. Logistic regression revealed that preoperative pain, bone surgery, and length of incision were risk factors for postoperative rebound pain, and patient-controlled analgesia was protective against postoperative rebound pain. Conclusion:. Tropisetron does not affect the incidence of rebound pain after peripheral nerve block. Patients at high risk of postoperative rebound pain should be identified for appropriate management. Registration site: www.chictr.org.cn (ChiCTR2300069994).